A class of simple tracially AF C*-algebras - N. E. Livingston (International Journal of Mathematics and Mathematical Sciences, 2002)
The concept of a tracially AF (TAF) C*-algebra was introduced recently to aid in the classification of nuclear C*-algebrasHere, we construct and study a broad class of inductive-limit C*-algebras. We give a numerical condition which, when satisfied, ensures that the corresponding algebra in our construction has the TAF property. We further give a necessary and sufficient condition under which certain of these C*-algebras are TAF.